PENGARUH PROFESIONAL AUDITOR TERHADAP KUALITAS AUDITOR - Kartini Hutagaol (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2023)
This study aims to see how the influence of professional auditors on the quality of auditors. Reports that can be trusted with good audit quality reduce fears of manipulation in the financial statements presented a company and can increase public confidence in the reliability of reports financial statements that have been audited by a public accountant. Findings in research that the professionalism of the auditor agrees to be implemented. This can be seen from the acquisition % auditor professionalism score of 72.40%. Furthermore, the findings about quality audit that the overall quality of the audit agrees to be carried out. Then that quality can build the credibility of information and quality of financial reporting information can help users to get useful information., this can be seen from the acquisition of % audit quality score of 75.11%. To see professional influence auditor on auditor quality is calculated using the SPSS program, with a value correlation coefficient of 0.538, this means that there is a relationship between auditor professionalism on audit quality. Correlation coefficient of 0.538 are in the medium category (0.40 - 0.5999). Next, the sig. = 0.02 less than 0.05 this shows that there is a significant relationship between auditor professionalism on audit quality. From the correlation table it is found that the value of p. value of 0.000 is below 0.05 this shows that even though the correlation coefficient is 0.538gives a moderate effect but based on statistical tests that there is a significant effect significant of the auditor's professionalism variable on audit quality Keywords : Professional Auditor, Quality Auditor